The Legal Certainty of Wakaf Without The Existence of A Wakaf Power Deed Made by The Officer Making The Wakaf Power Deed - Bhim Prakoso; Bayu Indra Permana; Isro Vita Nugraningsih; Clarissa Oktaviriya Prakoso (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
Donating property in Islam is good teaching, and it is even recommended for every capable Muslim individual to do it. This is because waqf is an act that has good characteristics and motivation, namely taqarrub to Allah SWT. This terminology means that a wakif must express his will (to donate his property) to the nazir, namely the waqf expressed orally and in writing. The meaning of the words